Defining consensus norms for palliative care of people with intellectual disabilities in Europe, using Delphi methods: A White Paper from the European Association of Palliative Care. (May 2016) - Tuffrey-Wijne, Irene; McLaughlin, Dorry; Curfs, Leopold; Dusart, Anne; Hoenger, Catherine; McEnhill, Linda; Read, Sue; Ryan, Karen; Satgé, Daniel; Straßer, Benjamin; Westergård, Britt-Evy; Oliver, David
Background: People with intellectual disabilities often present with unique challenges that make it more difficult to meet their palliative care needs. Aim: To define consensus norms for palliative care of people with intellectual disabilities in Europe. Design: Delphi study in four rounds: (1) a taskforce of 12 experts from seven European countries drafted the norms, based on available empirical knowledge and regional/national guidelines; (2) using an online survey, 34 experts from 18 European countries evaluated the draft norms, provided feedback and distributed the survey within their professional networks. Criteria for consensus were clearly defined; (3) modifications and recommendations were made by the taskforce; and (4) the European Association for Palliative Care reviewed and approved the final version. Setting and participants: Taskforce members: identified through international networking strategies. Expert panel: a purposive sample identified through taskforce members' networks. Results: A total of 80 experts from 15 European countries evaluated 52 items within the following 13 norms: equity of access, communication, recognising the need for palliative care, assessment of total needs, symptom management, end-of-life decision making, involving those who matter, collaboration, support for family/carers, preparing for death, bereavement support, education/training and developing/managing services. None of the items scored less than 86% agreement, making a further round unnecessary. In light of respondents' comments, several items were modified and one item was deleted. Conclusion: This White Paper presents the first guidance for clinical practice, policy and research related to palliative care for people with intellectual disabilities based on evidence and European consensus, setting a benchmark for changes in policy and practice.